Integrating distribution kinetics and toxicodynamics to assess repeat dose neurotoxicity in vitro using human BrainSpheres: a case study on amiodarone - Nunes, Carolina; Proença, Susana; Ambrosini, Giovanna; Pamies, David; Thomas, Aurélien; Kramer, Nynke I.; Zurich, Marie-Gabrielle (Frontiers in Pharmacology, 2023)
For ethical, economic and scientific reasons, animal experimentation used to evaluate the potential neurotoxicity of chemicals before their release on the market needs to be replaced by new approach methodologies (NAMs). To illustrate the use of NAMs, the human induced pluripotent stem cells (hiPSCs)-derived 3D model BrainSpheres was exposed acutely (48 h) or repeatedly (7 days) to amiodarone (0.625 -15 µM), a lipophilic antiarrhytmic drug reported to have deleterious effects on the nervous system. Neurotoxicity was assessed using transcriptomics, immunohistochemistry for cell typespecific markers and real-time reverse transcription-polymerase chain reaction (qRT-PCR) for various genes involved in lipid metabolism. By integrating distribution kinetics modelling with neurotoxicity readouts, we show that the observed time-and concentration-dependent increase in the neurotoxic effects of amiodarone is driven by the cellular accumulation of amiodarone after repeated dosing. The development of a compartmental in vitro distribution kinetics model allowed us to predict the change in cell-associated concentrations in BrainSpheres with time and for different exposure scenarios.Results suggest that human cells are intrinsically more sensitive to amiodarone than rodent cells. Amiodarone-induced regulation of lipid metabolism genes was observed in brain cells for the first time. Astrocytes appeared to be the most sensitive human brain cell type in vitro. In conclusion, assessing readouts at different molecular levels after repeat dosing of human iPSC-derived BrainSpheres in combination with compartmental modelling of in vitro kinetics provides a mechanistic means to assess neurotoxicity pathways and refine chemical safety assessment for humans.